Effectiveness of homogenization equipment on very large crude carrier vessel - Nordin, Haris Fadilla (2014)
The use of homogenizer in fuel treatment of heavy fuel oil on board merchant vessel is arguable; it will reduce separation efficiency of fuel contaminants and fuel properties. Therefore this research analyses the effectiveness of homogenizer operated in Very Large Crude Carrier (VLCC) vessel, MT Bunga Kasturi Lima. The aim of this research is to compare operational effects on the application of homogenizer against those without the use of homogenizer. The common method for fuel treatment on board the vessel is by using purifier. The separation of impurities and water from heavy fuel oil is essential for good combustion. Actual measurement was captured on board for sludge production, fuel oil sampling for purifier efficiency and fuel properties analyses and main engine exhaust gas sampling while the vessel was sailing from Singapore to Port of Sikka, India and then to Cape Town, South Africa. The range of sludge production reduction is between 17% to 23% compared to without homogenizer in operation. Purifier efficiency gives a result between 63% to 70% reduction of Aluminum and Silicon for untreated fuel (without homogenizer) and 42% to 50% for homogenized fuel (with homogenizer). The saving calculated from the operational data such as valuable fuel oil and less handling fees for sludge disposal were used for Net Present Value (NPV) analysis. The negative NPV was obtained and showed that the installation of homogenizer did not provide economic advantages. Furthermore it could be concluded that the effect from bunker fuel type, homogenizer positioning on board fuel treatment, vessel fuel consumption and sea state condition gave various impact on the effectiveness of homogenizer.